Spiritual and Religious Attitudes in Dealing with Illness in Polish Patients with Chronic Diseases: Validation of the Polish Version of the SpREUK Questionnaire - Büssing, Arndt (Journal of religion and health, 2016)
Although providing religious/spiritual (SpR) support to sick has received in Poland growing attention in the scientific literature, little has been written about how to measure whether patients are in search for SpR or may already have trust in such a resource helpful to cope with disease. The Polish version of the SpREUK questionnaire was validated in a sample of 275 patients with chronic diseases. Both explorative and confirmatory factor analysis confirmed the already established three subscales, i.e., Search, Trust, and Reflection, with good internal consistency coefficients (Cronbach’s α between .74 and .91). The instrument appears to be a good choice to be used in both secular and religious societies.